EDUCATION ABOUT DIET MANAGEMENT OF DIABETES MELLITUS TO ELDERLY AT THE ELDERLY POSYANDU, PELEM VILLAGE, KEDIRI DISTRICT - Erni Rahmawati; Dwi Rahayu; Astri Yunita; Atik Setiawan Wahyuningsih (Suluh Adiluhung Publisher (SAPub), 2024)
Diabetes Mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia due to abnormalities in insulin secretion, insulin action or both. The number of DM sufferers globally increases every year, the causes include increasing population, age, obesity, and lack of physical activity. Preventive measures that can be taken include education and regular health checks. To increase knowledge and understanding of elderly about hypertension and diabetes, one of the efforts made is to provide health education about hypertension and diabetes, as well as screening elderly in Pelem Village, Kediri District. In this activity, the results showed that there was increasing knowledge about diabetes of elderly, which was the addition of information and insight about health and provided a clear description for elderly regarding the prevention and management of diabetes through counseling and educational media in the form of leaflets.